Luxury Goods Taxation and Symbolic Redistribution: An Indonesian Case Study (Indonesian Tax Justice Review, 2024)
Luxury goods taxation is frequently promoted as a progressive policy tool capable of enhancing redistribution and reinforcing tax justice. This paper critically examines Indonesia’s Luxury Goods Sales Tax (LGST) to assess whether such claims withstand empirical and institutional scrutiny. Through qualitative policy analysis, the study interrogates the tax’s normative foundations alongside its operational design, focusing on tax base definition, rate structures, valuation practices, and enforcement capacity. The findings demonstrate that Indonesia’s LGST is structurally ill-equipped to function as an effective redistributive instrument. The tax base is narrowly defined and inconsistently applied, allowing high-income consumption to escape taxation through product reclassification, under-valuation, and substitution effects. Weak administrative oversight and enforcement further exacerbate these shortcomings, resulting in limited revenue generation and minimal impact on income or wealth inequality. Rather than correcting vertical inequities, the LGST largely reproduces existing fiscal asymmetries. This paper advances the critical argument that luxury taxation in Indonesia operates primarily as a mechanism of symbolic redistribution—a policy that performs progressivity rhetorically while failing to deliver substantive equity outcomes. The novelty of the study lies in exposing the disconnect between the moral and political appeal of luxury taxes and their actual redistributive performance in a developing-country context. By challenging the uncritical adoption of luxury taxation as a fairness-enhancing measure, the paper contributes to broader debates on progressive taxation and fiscal capacity in emerging economies. It concludes that without fundamental reforms to tax design, valuation standards, and enforcement institutions, luxury taxes risk functioning as symbolic gestures that obscure deeper structural deficiencies in tax systems.